2014
DOI: 10.1016/j.virol.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Nef-mediated down-regulation of CD4 and HLA class I in HIV-1 subtype C infection: Association with disease progression and influence of immune pressure

Abstract: Nef plays a major role in HIV-1 pathogenicity. We studied HIV-1 subtype C infected individuals in acute/early (n=120) or chronic (n=207) infection to investigate the relationship between Nef-mediated CD4/HLA-I down-regulation activities and disease progression, and the influence of immune-driven sequence variation on these Nef functions. A single Nef sequence per individual was cloned into an expression plasmid, followed by transfection of a T cell line and measurement of CD4 and HLA-I expression. In early inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(73 citation statements)
references
References 55 publications
(101 reference statements)
5
68
0
Order By: Relevance
“…More recently, a study of Ͼ100 clinical isolates showed that subtype D had higher Pol-driven replication capacity than subtype A and directly linked these differences to faster disease progression in the former than in the latter subtype (35). Furthermore, we recently demonstrated subtype-specific differ-ences in Nef function (36) and showed that Nef functional differences in acute infection correlate with markers of disease progression (37). Taken together, these results support subtype-specific differences in HIV-1 protein function as determinants of disease progression.…”
mentioning
confidence: 94%
“…More recently, a study of Ͼ100 clinical isolates showed that subtype D had higher Pol-driven replication capacity than subtype A and directly linked these differences to faster disease progression in the former than in the latter subtype (35). Furthermore, we recently demonstrated subtype-specific differ-ences in Nef function (36) and showed that Nef functional differences in acute infection correlate with markers of disease progression (37). Taken together, these results support subtype-specific differences in HIV-1 protein function as determinants of disease progression.…”
mentioning
confidence: 94%
“…HIV-1 contains a singlestranded RNA genome that is 9 kilobases in length and contains 9 genes that encode 15 different proteins (Mann et al, 2014). The major viral proteins (some of which contain >1 protein subunit) are classified as structural proteins (Gag, Pol, and Env), regulatory proteins (Tat and Rev), and accessory proteins (Vpu, Vpr, Vif, and Nef) (Greenway et al, 2002).HIV infection of a host cell begins with the binding of the virus particle (virion) to the host cell.…”
Section: Virologymentioning
confidence: 99%
“…Gag then functions in the budding of mature virions from the plasma membrane. The Nef protein acts on the cellular environment to promote replication by inhibiting the host immunologic response to HIV and inhibiting death of infected cells by apoptosis (Mann et al, 2014). (Mann et al, 2014).…”
Section: Virologymentioning
confidence: 99%
“…3C) for how the Loc-103275158 protein might combat Nef downregulation of MHC-I from the surface of tarsier cells infected by an appropriate primate lentivirus, i.e., after the mechanism of HIV-1 Nef in humans. 5,7,[19][20][21] Theoretically, a phosphorylation/dephosphorylation event within the CD loop would occur when the protein is in a "closed" conformation; based upon our modeled contacts, we prefer the notion that the MHC-I CD initially associates with some affinity to this closed conformation (left cartoon, Fig. 3C).…”
Section: Gov) H (Helix) Hth (Helix-turn-helix) Hss (Helix-strand-smentioning
confidence: 99%